2016
DOI: 10.5603/kp.a2016.0059
|View full text |Cite
|
Sign up to set email alerts
|

Association between anxiety and depression in patients with acute coronary syndromes due to financial crisis

Abstract: A b s t r a c t Background:The effect of anxiety and depression on patients with acute coronary syndromes (ACS) warrants investigation, especially during periods of economic crisis. Aim:To investigate the relation between anxiety and depression in patients presenting with ACS due to financial crisis and to investigate whether these two entities could predict long-term cardiovascular mortality. Methods and results:Anxiety and depression symptoms were assessed in 350 patients (210 men) presenting with ACS, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…At T1 and T2 differences in preceding measures of depression and anxiety among lifestyle clusters were assessed to explore the possible association of these psychological variables with subsequent behavioral change. Depression and anxiety have been selected for their significant associations to ACS onset and recurrence [ 15 16 ], and for their effect on patients’ likelihood to adhere to lifestyle modification programs and then to effectively quit smoking, adopt a healthier diet and be more physically active [ 17 20 ]. At each wave the associations between cluster membership and HR were also explored.…”
Section: Introductionmentioning
confidence: 99%
“…At T1 and T2 differences in preceding measures of depression and anxiety among lifestyle clusters were assessed to explore the possible association of these psychological variables with subsequent behavioral change. Depression and anxiety have been selected for their significant associations to ACS onset and recurrence [ 15 16 ], and for their effect on patients’ likelihood to adhere to lifestyle modification programs and then to effectively quit smoking, adopt a healthier diet and be more physically active [ 17 20 ]. At each wave the associations between cluster membership and HR were also explored.…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Supplementary Figure 1, 14 potentially eligible studies with a total of 89,176 patients were identified (Table 1) (see Supplementary References 4–7). 110 The risk of bias of each study is summarised in Supplementary Table 1. Extracted and calculated ORs/HRs are listed in Table 1.…”
mentioning
confidence: 99%
“…Adjusted ORs for early (one-day, 4 inhospital 6,7 and 30-day (see Supplementary Reference 5)) 8 mortality were available in five studies (see Supplementary Reference 5), 4,68 and adjusted HRs for overall (one-year 8 to 77-month (see Supplementary Reference 6)) mortality were available in eight studies (see Supplementary References 4 and 6). 1,2,5,810…”
mentioning
confidence: 99%
See 1 more Smart Citation